Pendampingan Strategi Parenting pada Masyarakat Desa Sinar Jaya Kecamatan Mandalawangi Menggabungkan Kearifan Lokal dan Metode Modern - Imamudin; Jessica Anastasya Simarmata; Elin Herlina; Nurul Prasasti Syiami; Naswa Cika Ananda; Sheilla Fahira Puspita; Muhamad Baelani; Faqih Fadlurrohman; Hermawan Prayoga; Edi Lesmana (Jurnal Ragam Pengabdian, 2024)
Parenting assistance in Sinar Jaya Village combines local wisdom with modern methods to improve the quality of childcare. This assistance aims to analyze the parenting strategies applied and their impact on children's development. The results of the assistance show that the combination of traditional values and modern approaches provides positive results in shaping the character of children who are independent, noble, and ready to face the challenges of the times. that this combination has a positive impact on child development, including improving children's social, emotional, and cognitive abilities. In addition, this mentoring also identifies challenges and opportunities in the implementation of these parenting strategies. that this combination has a positive impact on children's development, including improving children's social, emotional, and cognitive abilities. In addition, it also identifies challenges and opportunities in the implementation of these parenting strategies.